Proceedings of the 15th Conference of the European Chapter of The Association for Computational Linguistics: Volume 2 2017
DOI: 10.18653/v1/e17-2021
|View full text |Cite
|
Sign up to set email alerts
|

Optimal encoding! - Information Theory constrains article omission in newspaper headlines

Abstract: In this paper we argue that the distribution of article omission in newspaper headlines is constrained by information-theoretical principles (Shannon 1948). To this effect, we present corpus data and results from an acceptability rating study. Both point in the same direction: In our corpus, articles are significantly more frequent, when they precede a less predictable head noun. And subjects perceive article omission as more acceptable, if the head noun is (comparably) more predictable. This is in line with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The tendency to reduce predictable expressions has been observed on different levels of linguistic analysis, ranging from phonetics [1,[38][39][40][41][42][43][44][45][46][47] and morphology [48] to the omission of predictable words [4,[6][7][8][9]49]. If this principle applies to fragments as well, we expect that fragments are more strongly preferred over the corresponding full sentence if the omission of words that are predictable in a specific context results in a well-formed fragment.…”
Section: Predictability Effects On Omissions In Fragmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency to reduce predictable expressions has been observed on different levels of linguistic analysis, ranging from phonetics [1,[38][39][40][41][42][43][44][45][46][47] and morphology [48] to the omission of predictable words [4,[6][7][8][9]49]. If this principle applies to fragments as well, we expect that fragments are more strongly preferred over the corresponding full sentence if the omission of words that are predictable in a specific context results in a well-formed fragment.…”
Section: Predictability Effects On Omissions In Fragmentsmentioning
confidence: 99%
“…Throughout the last 15 years, predictability effects on the choice and realization of linguistic expressions have been evidenced for a variety of languages and levels of linguistic analysis. This encompasses the findings that predictable words are articulatorily reduced [1], read faster [2] and more often pronominalized [3] and omitted [4][5][6][7][8][9]. These predictability effects have motivated the more general insight that the probability of a word to appear in context is proportional to the effort required for processing it [10,11].…”
Section: Introductionmentioning
confidence: 95%
“…The Uniform Information Density (UID) hypothesis (Levy and Jaeger, 2007 ) has been successfully applied to account for a variety of omission phenomena from acoustic reduction (Aylett and Turk, 2004 ; see Jaeger and Buz, 2017 for an overview), to the omission of functional elements such as relativizers (Levy and Jaeger, 2007 ), complementizers (Jaeger, 2010 ) and discourse markers (Asr and Demberg, 2015 ) in English, case markers in Japanese (Kurumada and Jaeger, 2015 ) and articles in German newspaper articles (Lemke et al, 2017 ), to the omission of content words, for instance the deletion of parts of the utterance in German fragments (Lemke et al, 2020 ) and the omission of preverbal subjects in Russian (Kravtchenko, 2014 ). In a recent study, Lemke et al 2 found that UID also constrains other elliptical phenomena such as sluicing.…”
Section: Information-theoretic Account To Vp Ellipsismentioning
confidence: 99%
“…Information-theoretic processing constraints have been shown to explain the distribution of a wide range of reduction phenomena. Their application ranges from phonological reduction (Bell et al, 2003(Bell et al, , 2009Aylett and Turk, 2004;Demberg et al, 2012;Kuperman and Bresnan, 2012;Seyfarth, 2014;Pate and Goldwater, 2015;Brandt et al, 2017Brandt et al, , 2018Malisz et al, 2018) to morphological effects on contraction (Frank and Jaeger, 2008) and case marker omission (Kurumada and Jaeger, 2015;Norcliffe and Jaeger, 2016) to pronominalization (Tily and Piantadosi, 2009), and, what is most closely related to omissions in fragments, optional omissions of various types of function words (Levy and Jaeger, 2007;Jaeger, 2010;Asr and Demberg, 2015;Lemke et al, 2017) and preverbal subjects (Kravtchenko, 2014;Schäfer, 2021).…”
Section: An Information-theoretic Account Of Fragment Usagementioning
confidence: 99%
“…However, Lemke et al (2021) did not look into the more fine-grained predictions of the information-theoretic account on the word level. Second, information-theoretic constraints have been shown to explain the distribution of omissions particularly on the word level, such as those of complementizers, pronouns, articles and case markers (Levy and Jaeger, 2007;Frank and Jaeger, 2008;Jaeger, 2010;Asr and Demberg, 2015;Kurumada and Jaeger, 2015;Norcliffe and Jaeger, 2016;Lemke et al, 2017). Even though most of these studies focused on semantically relatively empty function words, 2 information-theoretic constraints make similar predictions on the omission of content words.…”
Section: Introductionmentioning
confidence: 98%